AN ASSESSMENT OF THE IMPACT OF TOTAL QUALITY MANAGEMENT PRACTICES AT PARKVIEW PREMIER CLINICAL LABORATORIES (Singaporean Journal of Business Economics and Management, 2014)
Stiff competition in a tough economic environment was a key driver for Parkview Clinical Laboratories to introduce total quality management (TQM) as an integrated management approach to continuously improve performance of products, processes and services ultimately yielding and surpassing customers' expectations. This study sought to assess the impact of TQM practices in improving healthcare service delivery at Parkview Clinical Laboratories against the Stepwise Laboratory Improvement Process towards Accreditation (SLIPTA) framework. Other drivers for TQM included but not limited to: increased customer complaints as a result of delayed turnaround times, unreliable service delivery and erroneous laboratory results.Literature on total quality management principles such as Kaizen stepwise continuous improvement, Lean management and six sigma principles and the WHO-AFRO SLIPTA model provided a framework for the study. The study conducted a baseline study against the SLIPTA constructs to measure service quality at three intervals. A customer survey was done to obtain quantitative data pertaining to customer needs and satisfaction whose constructs were guided by the gap model. Research elements were stratified according to profession to ensure representation of various services. To assess customer satisfaction whose constructs were guided by the gap model, and also to capture customer needs and complaints, the quantitative approach was also adopted. This enabled responses to be statistically analysed to determine their significant levels and to classify the need and complaints of gap analysis.The quantitative research approach was also chosen after considering the large sample size, in order to provide accurate and valid data representative of the target population using structured instruments like questionnaires.Customer surveys sought to identify and group the customer needs decision making. Hence quantitative analysis of the complaints was very important to measure the gravity of service gaps.